O estudo do comportamento verbal no Brasil: uma análise com base em resumos de dissertações e teses - Fidalgo, Adriana Piñeiro (2011)
The purpose of this dissertation was to evaluate how the verbal behavior study, based on the Skinner (1957) proposal, was established and conducted in Brazil. For that, this study performed a historical revision of Brazilian dissertations and theses related to the subject and carried out from 1969 to 2007. The aspects investigated include: (a) number of dissertation and thesis related to the subject, (b) thesis advisor, (c) type of research (descriptive or experimental), (d) line of research (basic, applied, conceptual and historical), (e) concepts of the Behavior Analyses, (f) area of application, (g) subjects, (h) units of analyses and measures, (i) designs of single subject or group design, and (j) participants. It was analyzed how such aspects varied over the years and the appropriateness of the methodological aspects employed in research, based on Skinner's propositions (1957). The publications (articles, abstracts in scientific events and book chapters) based on dissertations and theses were also investigated in order to estimate the diffusion of knowledge. In total, 141 dissertations and 41 theses related to the subject were identified. The Universidade de São Paulo produced the largest number of studies, and was primarily responsible for expanding such research field in the country; forming and exporting thesis advisors for other institutions of higher education. Other major research centers identified were: UnB, UFSCar, UFPA, PUC-SP, UCG and UEL. The researchers identified by the large number of orientations in this field of study are: Carolina Bori, Deisy das Graças, Emmanuel Tourinho, Maria Amália Andery, Roberto Banaco, Maria Amélia Matos, Antônio Ribeiro, and Júlio de Rose. Of the 182 studies reviewed, 104 were applied research, 63 were basic, and 15 were historical and conceptual research. The most recurrent themes were: operant control of verbal behavior, rule-governed behavior, stimulus equivalence, correspondence between verbal and nonverbal behavior, and finally, functional hypotheses about the possible control variables involved in verbal behavior. Generally, Brazilian dissertations and theses about verbal behavior have followed the methodological model proposed by the Behavior Analysis field, consisting of experimentation, design of single subject, and unit of functional analysis. Only 51% of the analyzed studies were published, indicating the need to expand the dissemination of the knowledge produced by behavior analysts. The results obtained in this research allow to say that the study of verbal behavior in Brazil was established as a research program and has grown over the years, following the expansion of the Behavior Analysis through the country